Mixing state of atmospheric particles over the North China Plain. (January 2016) - Zhang, S.L.; Ma, N.; Kecorius, S.; Wang, P.C.; Hu, M.; Wang, Z.B.; Größ, J.; Wu, Z.J.; Wiedensohler, A.
Abstract: In this unique processing study, the mixing state of ambient submicron aerosol particles in terms of hygroscopicity and volatility was investigated with a Hygroscopicity Tandem Differential Mobility Analyzer and a Volatility Tandem Differential Mobility Analyzer. The measurements were conducted at a regional atmospheric observational site in the North China Plain (NCP) from 8 July to 9 August, 2013. Multimodal patterns were observed in the probability density functions of the hygroscopicity parameter κ and the shrink factor, indicating that ambient particles are mostly an external mixture of particles with different hygroscopicity and volatility. Linear relationships were found between the number fraction of hydrophobic and non-volatile populations, reflecting the dominance of soot in hydrophobic and non-volatile particles. The number fraction of non-volatile particles is lower than that of hydrophobic particles in most cases, indicating that a certain fraction of hydrophobic particles is volatile. Distinct diurnal patterns were found for the number fraction of the hydrophobic and non-volatile particles, with a higher level at nighttime and a lower level during the daytime. The result of air mass classification shows that aerosol particles in air masses coming from north with high moving speed have a high number fraction of hydrophobic/non-volatile population, and are more externally mixed. Only minor differences can be found between the measured aerosol properties for the rest of the air masses. With abundant precursor in the NCP, no matter where the air mass originates, as far as it stays in the NCP for a certain time, aerosol particles may get aged and mixed with newly emitted particles in a short time. Highlights: A HTDMA and a VTDMA were used together in a unique field study in China. A certain fraction of hydrophobic particles is volatile. Minor difference was found between the mixing states for different air mass types. Submicron particles in North China Plain are external mixture of two major groups.